Polyribosomal and particulate distribution of lysyl- and phenylalanyl-transfer ribonucleic acid synthetases - Moline, Gale (1974)
1. Only two aminoacyl-tRNA synthetases from Chinese hamster ovary cells are found associated with ribosomes and polyribosomes. 2. Phenylalanyl-tRNA synthetase activity is found with the 60S subunit, 80S monoribosome and individual polyribosomes. An additional 15S form of the enzyme is also seen. 3. Lysyl-tRNA synthetase activity is found in a form of about 20S and associated with ribosomal subunits and polyribosomes. The ribosomal subunits having lysyl-tRNA synthetase activity are about 6S larger than the bulk of the ribosomal subunits. 4. The lysyl- and phenylalanyl-tRNA synthetases found in different complexes have differential sensitivity to EDTA and centrifugation properties.